STRATEGI KOMUNIKASI PT INDOLAKTO DALAM MENINGKATAN PENJUALAN PRODUK INDOESKRIM - Demus, Nico; Suryawati, I Gusti Agung Alit; Pradipta, Ade Devia (E-Jurnal Medium, 2024)
Creative strategy is a planning carried out to achieve a specific goal to be achieved in an advertising. The problems want to be appointed is the thing that concerned with creative strategy Indoeskrim Nusantara "Kisah Legenda Nusantara" ads in cooperation with MullenLowe Indonesia as advertising agency that created the ads. While the aim of research is to find out how creative advertising strategy "Kisah Legenda Nusantara" ads to build brand awareness for Indoeskrim Nusantara. Researchers also use the Belch theory for the exploration of big ideas and the attractiveness of advertising. And using theory advertising in Morrisan’s book that describes ad execution.The research method used is a case study with a type of descriptive research and qualitative approaches. Techniques of data collection was in-depth interviews with some of the data sources and some documentation writers. The results of the study conclude that the creative strategy of the advertisement "Kisah Legenda Nusantara" uses the appeal of 'superior sense' (rational) of authentic Indonesian taste and the emotional appeal of integration that uses a contradictory combination of colossal (nostalgic) and contemporary elements (relevance). In execution in absurd humor, slice of life and dramatization.